2012
DOI: 10.1534/genetics.111.137083
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Genomic and Epigenetic Signals in the Maintenance and Inheritance of Heterochromatin Domains in Fission Yeast

Abstract: Many essential aspects of genome function, including gene expression and chromosome segregation, are mediated throughout development and differentiation by changes in the chromatin state. Along with genomic signals encoded in the DNA, epigenetic processes regulate heritable gene expression patterns. Genomic signals such as enhancers, silencers, and repetitive DNA, while required for the establishment of alternative chromatin states, have an unclear role in epigenetic processes that underlie the persistence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It therefore remains to be determined whether H3K9 methylation can be inherited independently of specific DNA sequences or modulation of H3K9 demethylase activity in mammalian cells. Also, in fission yeast, a previous study reported that ectopic heterochromatin-dependent silencing of an ade6 + allele induced by a centromeric DNA fragment is maintained in an RNAi-dependent manner after excision of the centromeric DNA fragment (47), suggesting that a small RNA amplification loop may somehow be established at the ade6 + locus which helps maintain the silent state. However, these findings contradict other studies, which have demonstrated that silencing of ura4 + alleles by the generation of small RNA from a hairpin could not be maintained in the absence of the inducing hairpin (48, 49).…”
Section: Discussionmentioning
confidence: 99%
“…It therefore remains to be determined whether H3K9 methylation can be inherited independently of specific DNA sequences or modulation of H3K9 demethylase activity in mammalian cells. Also, in fission yeast, a previous study reported that ectopic heterochromatin-dependent silencing of an ade6 + allele induced by a centromeric DNA fragment is maintained in an RNAi-dependent manner after excision of the centromeric DNA fragment (47), suggesting that a small RNA amplification loop may somehow be established at the ade6 + locus which helps maintain the silent state. However, these findings contradict other studies, which have demonstrated that silencing of ura4 + alleles by the generation of small RNA from a hairpin could not be maintained in the absence of the inducing hairpin (48, 49).…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be challenging to pinpoint specific causal genetic differences between cells despite increasingly powerful sequencing technologies (Zong et al, 2012). Furthermore, non-genetic causes of variant phenotypes can persist for several cell divisions, and some perdure even through meiosis (Greer et al, 2011; Nakayama et al, 2000; Pillus and Rine, 1989; Wheeler et al, 2012), although genomes were not sequenced in this case.…”
Section: Introductionmentioning
confidence: 97%
“…Some studies suggest that sequence specific elements and the RNA systems involved are required for maintenance of heterochromatin status [24]. However, recent work in yeast and worms suggests that heritable gene expression states and structural heterochromatin (H3K9me2/3) can be maintained in the absence of cis nucleating sequences or the original stimulus [25][27]. Drosophila melanogaster , a multicellular system with complex development, is a good choice for investigating this question.…”
Section: Introductionmentioning
confidence: 99%